Praktik Gadai Lahan Dan Dampaknya Terhadap Kesejahteraan Al-Rahin Di Desa Gapura Kecamatan Pujut Kabupaten Lombok Tengah - Yasin, Muaidy; Huzaini, Muhammad; Jufri, Akhmad (Jurnal Ekonomi dan Bisnis, 2018)
This study aims to find out and analyze the factors that cause a person to mortgage his land, how to implement a mortgage, whether the mortgage practice is in accordance with Islamic law and how the level of welfare of al-rahin in Gapura Village, Pujut District, Central Lombok Regency. This research uses qualitative methods, because it examines reality, phenomena or symptoms that are holistic / intact, complex, dynamic and meaningful. Data collection techniques are carried out in natural conditions and carried out by means of observation, in-depth interviews and documentation in the form of sound recordings and photographs. Informants are set while in the field using snowball sampling techniques. Data analysis used is qualitative analysis. Research conclusion 1. Most farmers practice land pawning due to financial constraints and to obtain business capital; 2. The practice of pawning in Gapura Village, Pujut Subdistrict, is more colored by adat, which is a hereditary habit from its predecessors; 3. The practice of land pledges in Gapura Village, Pujut Subdistrict, is in accordance with the pillars and pawning conditions according to Islam, but if seen from the use of collateral goods, it is not in accordance with the pawning principle according to Islam, because it creates injustice between al-rahin and al-murtahin ; 4. Most of the pledges (al-rahin) in Gapura Village, Pujut Subdistrict, have not prospered from the perspective of Islam, and the part is already getting Islamic welfare, because the needs of dharuriyyat and hajiyat are fulfilled